Data transmission system with encryption by chaotic sequences - Politans’kyy, R. L.; Shpatar, P. M.; Hres, A. V.; Verigha, A. D. (Technology and design in electronic equipment, 2014)
Protection of transferable information in the telecommunication systems is possible by its imposition of coding sequence on a plaintext. Encryption of pseudorandom sequences can be performed by using generation algorithms which are implemented on the basis of the phenomenon of dynamical chaos, which is sensitive to changes in the initial conditions. One of the major problems encountered in the construction of secure communication systems is to provide synchronization between the receiving and transmitting parties of communication systems. Improvement of methods of hidden data transfer based on the systems with chaotic synchronization is the important task of research in the field of information and telecommunication systems based on chaos.This article shows an implementation of a data transmission system, encrypted by sequences, generated on the basis of one-dimensional discrete chaotic maps with ensuring synchronization of the transmitting and receiving sides of the system. In this system realization of synchronization is offered by a transmission through certain time domains of current value of xn generated by a logistic reflection. Xn transmission period depends on computer speed and distance between subscribers of the system. Its value is determined by transmitting a test message before the session. Infallible reception of test message indicates the optimal choice of a transmission period of the current value of xn. Selection period is done at the program level. For the construction of communication network modern software was used, in particular programming language Delphi 7.0. The work of the system is shown on the example of information transmission between the users of the system. The system operates in real time full duplex mode at any hardware implementation of Internet access. It is enough for the users of the system to specify IP address only.